PENERAPAN MODEL PEMBELAJARAN ECOLA DALAM MENINGKATKAN KEMAMPUAN MEMBACA CEPAT SISWA - Fitria, Yoza; Eli Rustinar; Hasmi Suyuthi; Reni Kusmiarti; Adi Asmara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze students’ speed reading skills before and after the implementation of the Extending Concepts through Language Activities (ECOLA) learning model and to determine the effectiveness of this model in improving the speed reading skills of seventh-grade students in Class 7A at Seluma State Junior High School No. 2. This study was motivated by the students’ low speed reading skills, as indicated by a reading speed of 50-60 words per minute, a reading comprehension rate of 20%, and an average reading skill score of 51.83. This study employed a quantitative approach using an experimental method and a pre-experimental one-group pretest-posttest design. The research subjects consisted of 27 students in Class VII A at Seluma State Junior High School 2. Data collection was conducted through speed reading ability tests before (pretest) and after (posttest) the implementation of the ECOLA model. The data were analyzed using descriptive statistics, a normality test, and a paired-sample t-test. The results showed that the mean pretest score of 50.22 fell into the “below average” category, while the mean posttest score increased to 78.85, falling into the “good” category. The results of the normality test showed that the data were normally distributed, while the results of the paired-sample t-test yielded a significance value of 0.000 < 0.05, indicating a significant difference in students’ speed reading ability before and after the implementation of the ECOLA model.